Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Pelayanan Pada PT. Pos Indondesia (Persero) Sumatera Utara - Tutri Mawar Aqdilla; Riyan Pradesyah (Jurnal Manajemen Akuntansi (JUMSI), 2022)
In meeting the needs and desires will achieve a high level of Service. Quality of Service is a dynamic condition and relates to products, services, people, processes and the environment that meet or exceed expectations. Service quality also has the expected level of excellence and control over the level of excellence and can meet the desires and needs.The purpose of this study is to determine the factors that affect the quality of service at PT. Pos Indonesia (Persero) North Sumatra.The sample in this study as many as 100 employees who are in PT. Pos Indonesia (Persero) North Sumatra. This study was collected through questionnaires processed and dynamic by using multiple regression. Then do the reward test used in the validity test by using the Corrected Item Total and reliability test in using Cronbach Alpha.To test the hypothesis in this study.This research uses t test, f test, and determination test. The results in this study indicate that there is a positive and significant influence variable variable reward to variable salary indicated thitung (7.891) > ttable (1.660) with a significant value of 0.000 < 0.05, positive and significant influence variable salary to variable quality of Service indicated by thitung (7.247) > ttable (1.660) with a significant value of 0.000 < 0.05, and simultaneously indicate that reward, salary and quality of Service indicated by the value Fhitung (189.572) > ftable (3.08) with a significant rate of 0.000. Furthermore, the value of R square is equal to 0.796 or 7.96%. The rest is influenced by variables that are not examined in this study.